Student copula method in rainfall distribution - Sahrin, Sharainie (2015)
Copulas are tools for modelling dependence of several random variables. The term copula was first used in the work of Sklar (1959) and is derived from the latin word copulare, to connect or to join. The main purpose of copulas is to describe the interrelation of several random variables. (Thorsten Schmidt, 2006). Copula is a function that joins the two distributions and known as dependence functions. Copula connect multivariate distribution function to its univariate marginal distribution. When we have two models having the problems relating to dependence, we can join that models becoming one model using marginal function. So, the dependency is taken care. It means that copula played an important role to join multivariate distributions to their one dimensional marginal distribution function.